De-facto Gaps in Social Protection for Standard and Non-standard Workers: An Approach for Monitoring the Accessibility and Levels of Income Support - Herwig Immervoll; Rodrigo Fernandez; Raphaela Hyee; Jongmi Lee; Daniele Pacifico (Institute of Labor Economics (IZA), 2022)
Social protection systems play a key stabilising role for individuals and societies, especially in the recent context of heightened uncertainties. Income stabilisation and related social policy objectives hinge on the extent to which social protection is accessible for those requiring support. This paper proposes a new empirical approach for quantifying the accessibility and value of income transfers following an earnings loss. It first presents a methodology for assessing support levels for jobless individuals in specific circumstances that allows for comparisons across countries and over time. It then illustrates the approach using longitudinal survey data in 16 OECD countries. The illustration focusses on differences in entitlements between people who were in "standard" and "non-standard" employment prior to joblessness. Results show that, prior to the COVID pandemic, income support gaps between standard and non-standard workers were often sizeable. For instance, in Korea, job losers with prior standard employment were nearly twice as likely to receive income support as otherwise similar individuals with a history of non-standard work. Gaps were also large in Italy and Portugal. By contrast, gaps were statistically insignificant in Australia, Austria, Belgium, Germany, Hungary and the United Kingdom. As these latter countries follow very different social protection strategies, results suggest that limiting support gaps for non-standard workers is achievable with different policy designs and targeting mechanisms.
Keywords: I38; J65; H55; H53; C31; C35; 330; cash benefits; social insurance; redistribution; poverty; coverage; adequacy